2018
DOI: 10.1016/j.jvs.2016.12.112
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs signature correlates with positive [18F]fluorodeoxyglucose-positron emission tomography in patients with abdominal aortic aneurysm

Abstract: Six miRNAs were identified as potential new circulating biomarkers of PET+ AAA. Three of these were similarly modulated in the metabolically active aneurysmal wall and might be directly involved in AAA instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…A total of 158 published articles were retrieved during the study period. After applying the exclusion criteria, 35 articles were finally included with full text reviewed (Figure ) . If aligned based on the date of publication, it was observed that the number of studies addressing miR‐125b and vascular diseases increases gradually over time since the first report that was published in 2010 (Figure ).…”
Section: Microrna‐125b In Vascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 158 published articles were retrieved during the study period. After applying the exclusion criteria, 35 articles were finally included with full text reviewed (Figure ) . If aligned based on the date of publication, it was observed that the number of studies addressing miR‐125b and vascular diseases increases gradually over time since the first report that was published in 2010 (Figure ).…”
Section: Microrna‐125b In Vascular Diseasesmentioning
confidence: 99%
“…MiR‐125b is no exception in this perspective. During our systematic literature search, we identified 12 articles examining the diagnostic utility of miR‐125b in different types of cardiovascular diseases, with the first report published 5 years ago (Table ) . Among these diseases, we found that coronary artery disease/coronary events (n = 4) and acute stroke (n = 3) are the most common diseases in which the role of circulating miR‐125b has been investigated, followed by intracranial aneurysms (n = 2), abdominal aortic aneurysm (n = 1), heart failure (n = 1) and VC (n = 1) (Table ).…”
Section: Microrna‐125b: a Potential Biomarker For Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is also regulated by molecular mechanisms [ 7 , 12 ]. Recent studies have revealed that the expression profile of many miRNAs differs significantly in patients with coronary aneurysms and aortic aneurysms [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 18 Fluoro-deoxy-glucose positron emission tomography/computed tomography ( 18 FDG-PET/CT) is associated with inflammatory response in aortic aneurysms and may be an independent parameter for the prediction of rupture. [ 2 3 ] However, its use is often overlooked except in malignant cases. We present an interesting case that, the decision of prophylactic surgery was facilitated by 18 FDG-PET/CT.…”
Section: Introductionmentioning
confidence: 99%